La metáfora de la pirámide deportiva: el efecto trickle down y up en españa - Seguí-Urbaneja, J.; Inglés, E.; Alcaraz, S.; De Bosscher, V. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2020)
The sports pyramid metaphor (trickle down and trickle up effect) has been used by several governments to justify their public investments in elite sport. The scientific evidence of this effect is fragmented; previous studies question its veracity. This study examines the effect of the sports pyramid metaphor in Spain. Using Spearman's correlation coefficient (p), we tested for possible relationships between sporting success and the evolution of the federation membership history of 23 sports modalities during 1992-2016. According to results, three different groups of sports could be identified: 1) those that could be assumed to present both trickle down and up effects; 2) those with negative correlations between sporting success and membership figures; and 3) sports that do not show any relationships between those variables. As a conclusion, it is stated that there is no clear and generalized evidence to confirm the existence of the sport pyramid metaphor in Spain.